TARBIYA DARSLARIDA 5-7-SINF OʻQUVChILARIDA KITOBXONLIK MADANIYATINI RIVOJLANTIRISh NATIJADORLIGI - Eshimbetov, O. (SCIENCE and SOCIETY, 2025)
Improvement of the effectiveness of developing reading culture in upbringing lessons in grades 5-7 in the formation of reading culture in learners, the system of methodological (working with text, analysis, review, discussion) and didactic support (reading program, fiction, dictionary, encyclopedia) based on the integration of continuous and regular stimulating strategies for reading (book selection, active learner, reading screen, information card, conference).
Keywords: reading program; fiction; dictionary; encyclopedia; speech culture; motivation; reading view; introductory reading; learning reading; reading culture